2018
DOI: 10.3390/molecules23123176
|View full text |Cite
|
Sign up to set email alerts
|

Computational Characterization of Bidentate P-Donor Ligands: Direct Comparison to Tolman’s Electronic Parameters

Abstract: The applicability of two types of transition-metal carbonyl complexes as appropriate candidates for computationally derived Tolman’s ligand electronic parameters were examined with density functional theory (DFT) calculations employing the B97D3 functional. Both Pd(0)L2(CO) and HRh(I)L2(CO) complexes correlated well with the experimental Tolman Electronic Parameter scale. For direct comparison of the electronic effects of diphosphines with those of monophosphines, the palladium-containing system is recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…[5][6][7][8][9] The broad range of applications of organometallic compounds in catalytic processes originates from their favorable redox properties, which can be easily tuned and optimized to the specific chemical process of interest by alteration of the metal center but even more importantly, by structural modification of the ligand sphere. With respect to the oxidative addition reaction, the addition of strongly coordinating σ-donor ligands such as phosphines, [10] N-heterocyclic carbenes [11] or bidentate nitrogen-containing molecules, [12] can be beneficial to enhance the chemical stability and, thus, the long-term performance of the molecular catalyst, as well as to provide a handle for tuning the oxidation potential of the metal center, and in consequence, the catalytic turnover. [13] Sawamura et al [14] discovered that the yields of Rh-catalyzed borylation with assisting phosphine ligand increased by approximately 10 % compared to phosphine-free conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] The broad range of applications of organometallic compounds in catalytic processes originates from their favorable redox properties, which can be easily tuned and optimized to the specific chemical process of interest by alteration of the metal center but even more importantly, by structural modification of the ligand sphere. With respect to the oxidative addition reaction, the addition of strongly coordinating σ-donor ligands such as phosphines, [10] N-heterocyclic carbenes [11] or bidentate nitrogen-containing molecules, [12] can be beneficial to enhance the chemical stability and, thus, the long-term performance of the molecular catalyst, as well as to provide a handle for tuning the oxidation potential of the metal center, and in consequence, the catalytic turnover. [13] Sawamura et al [14] discovered that the yields of Rh-catalyzed borylation with assisting phosphine ligand increased by approximately 10 % compared to phosphine-free conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the computed electronic parameter (CEP), that is the total symmetric (A) carbonyl stretching frequency in the Ni(CO) 3 L complex type, was calculated for ligand L1 ( Figure 4 ). The obtained value was ν A = 2083.2 cm −1 , which is in between the CEPs of triphenyl phosphite (ν A = 2085.3 cm −1 ) and trimethyl phosphite (ν A = 2079.5 cm −1 ), calculated at the same level of theory [ 45 ]. Since this parameter is a generally accepted measure for the Lewis basicity of P-donor ligands, we concluded that the new tris-BINOL-neomenthol monophosphites are expected to present a stronger Lewis base character compared with that of triphenyl phosphite.…”
Section: Resultsmentioning
confidence: 75%
“…The S4' parameter (ΣR 1 -P-R 2 − ΣNi-P-R) provides an insight into the strain exerted by the bulk on the Ni−P bond. Plotted against Tolman's electronic parameter, 47 we get a visualization of phosphine ligand space.…”
Section: ■ Theoretical Studies On Electronic and Steric Properties Of...mentioning
confidence: 99%